Composite polymer solid electrolyte and method for preparing the same

CN122992167APending Publication Date: 2026-10-27SHANGHAI HENGSOLI NEW ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611231604.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-14
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,由于无机材料与有机聚合物之间存在明显的界面性质差异,二者相容性较差,在复合过程中容易产生颗粒团聚、界面空隙及局部相分离等问题,反而增大离子传输阻抗;此外,无机陶瓷材料通常密度较高,大比例添加会降低电解质膜的质量能量密度,同时增加加工难度、加剧膜的脆化,不利于柔性固态电池及规模化制造

Benefits of technology

[0031]1、本发明提供的复合聚合物固态电解质,采用与含氟聚合物基体同属有机体系的含氟聚醚活性有机微粒作为增强相填料,摒弃了传统无机填料,二者可发生分子级别的物理缠结与润湿,消除了无机-有机复合中普遍存在的微观孔隙及界面缺陷,构建出连续、低阻抗的锂离子传输通道,从根本上解决了无机填料与聚合物基体相容性差的问题,降低了界面阻抗。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992167A_ABST
    Figure CN122992167A_ABST
Patent Text Reader

Abstract

The application discloses a kind of composite polymer solid electrolyte and preparation method thereof.The composite polymer solid electrolyte includes polymer matrix, fluorine-containing polyether active organic microparticle and conductive lithium salt;Fluorine-containing polyether active organic microparticle is prepared by copolymerization of polyethylene glycol methyl ether methacrylate and fluorine-containing acrylic monomer, particle size is 200nm-5μm, lithium salt accounts for 20wt%~50wt% of the total mass of composite polymer solid electrolyte, the fluorine-containing polyether active organic microparticle accounts for 2.5wt%~40wt% of the total mass of composite polymer solid electrolyte, and the balance is polymer matrix.The composite polymer solid electrolyte provided by the application uses fluorine-containing polyether active organic microparticle of the same organic system as fluorine-containing polymer matrix as reinforcing phase, and molecular level physical entanglement and wetting can occur between the two, eliminating the interface defects in inorganic-organic composite;Ether oxygen chain segment in microparticle promotes lithium salt dissociation, and fluorine-containing structure improves oxidation stability, so as to improve ionic conductivity, reduce interface impedance while considering the mechanical flexibility and electrochemical stability of membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of solid electrolyte technology for lithium-ion batteries, and specifically relates to a composite polymer solid electrolyte and its preparation method. Background Technology

[0002] With the rapid development of new energy vehicles, smart grids, and large-scale energy storage, lithium-ion batteries, as one of the mainstream energy storage technologies, have been widely used in portable electronic devices, electric vehicles, and energy storage systems. However, traditional lithium-ion batteries use organic liquid electrolytes as ion transport media, which pose safety hazards such as electrolyte leakage, flammability, volatility, and insufficient thermal stability. Under the application requirements of high energy density, high rate capability, and long cycle life, they are gradually failing to meet the development requirements of high-safety and high-performance energy storage devices.

[0003] Solid-state lithium batteries use solid electrolytes instead of traditional liquid electrolytes, effectively reducing the risk of internal short circuits and thermal runaway. They also offer higher safety, a wider electrochemical stability window, and potential high energy density, making them a key development direction for next-generation lithium battery technology. Among these, polymer solid electrolytes are widely studied due to their good flexibility, excellent interfacial contact capabilities, and ease of processing into films. Common systems include polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyacrylonitrile (PAN), and polymethyl methacrylate (PMMA).

[0004] Fluoropolymer solid electrolytes, represented by PVDF and PVDF-HFP, possess high mechanical strength, good chemical stability, and a wide electrochemical stability window. However, PVDF polymers have strong molecular chain regularity and a high tendency to crystallize, causing lithium ions to migrate mainly through limited amorphous regions, which limits the room-temperature ionic conductivity of the system. At the same time, during long-term cycling, a large and continuously increasing interfacial impedance is easily generated between the polymer electrolyte and the positive and negative electrodes, affecting the rate performance and cycle stability of the battery.

[0005] To address the aforementioned issues, existing technologies typically employ inorganic ceramic fillers to modify the polymer matrix, such as introducing inorganic particles like alumina (Al₂O₃), silicon dioxide (SiO₂), lithium lanthanum zirconium oxide (LLZO), and lithium lanthanum zirconium silicon phosphorus (LLZSP). Inorganic fillers can improve polymer electrolyte performance to some extent by reducing polymer crystallinity, providing additional lithium-ion migration channels, and enhancing mechanical strength. However, due to the significant differences in interfacial properties between inorganic materials and organic polymers, their compatibility is poor, easily leading to problems such as particle agglomeration, interfacial voids, and localized phase separation during the composite process, which in turn increases ion transport impedance. Furthermore, inorganic ceramic materials typically have high density; adding a large proportion reduces the mass energy density of the electrolyte membrane, increases processing difficulty, and exacerbates membrane embrittlement, which is detrimental to flexible solid-state batteries and large-scale manufacturing.

[0006] It is evident that existing polymer solid electrolytes still generally suffer from insufficient room temperature ionic conductivity, high interfacial impedance, poor compatibility and easy agglomeration and embrittlement when modified with inorganic fillers, making it difficult to balance ion transport performance, mechanical properties and electrochemical stability. Summary of the Invention

[0007] To address the problems existing in the prior art, the present invention aims to provide a composite polymer solid electrolyte and its preparation method.

[0008] The first aspect of this invention provides a composite polymer solid electrolyte, comprising:

[0009] Polymer matrix;

[0010] Fluorinated polyether active organic microparticles, wherein the fluorinated polyether active organic microparticles are prepared by copolymerization of polyethylene glycol methyl ether methacrylate and fluorinated acrylate monomers, and the particle size is 200 nm to 5 μm;

[0011] Conductive lithium salt;

[0012] The lithium salt accounts for 20wt% to 50wt% of the total mass of the composite polymer solid electrolyte, the fluorinated polyether active organic microparticles account for 2.5wt% to 40wt% of the total mass of the composite polymer solid electrolyte, and the remainder is the polymer matrix.

[0013] In one embodiment of the present invention, the fluorinated polyether active organic microparticles account for 5 wt% to 50 wt% of the total mass of the polymer matrix and the polymeric organic microparticles.

[0014] In one embodiment of the present invention, the polyethylene glycol methyl ether methacrylate has a number-average molecular weight of 300-1000 g / mol, more preferably 400-600 g / mol, and its general structural formula is CH2=C(CH3)COO(CH2CH2O)nCH3, where n is 3-20.

[0015] In one embodiment of the present invention, the polymer matrix is ​​selected from at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyacrylonitrile, and polymethyl methacrylate.

[0016] In one embodiment of the present invention, the fluorinated acrylate monomer is trifluoroethyl methacrylate.

[0017] In one embodiment of the present invention, the conductive lithium salt is at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium dioxalate borate, and lithium difluorooxalate borate.

[0018] The second invention provides a method for preparing the above-mentioned composite polymer solid electrolyte, comprising the following steps:

[0019] Step S1: Polyethylene glycol methyl ether methacrylate, fluorinated acrylate monomers, lithium salt and thermal initiator are mixed in a mass ratio of 100:(10-20):(10-40):(0.8-2) to obtain a mixed raw material;

[0020] Step S2: Bulk free radical polymerization is carried out at 60℃~100℃ for 5.5h~24h under an inert atmosphere, and polymer bulk is obtained after the reaction is completed;

[0021] Step S3: Grind and sieve the polymer block to obtain fluorinated polyether active organic microparticles with a particle size of 200 nm to 5 μm after sieving.

[0022] In step S4, a composite polymer solid electrolyte membrane is formed by using a solution casting method or a dry hot rolling method to combine the polymer matrix, the fluorinated polyether active organic microparticles obtained in step S3, and the conductive lithium salt.

[0023] In one embodiment of the present invention, the thermal initiator in step S1 is azobisisobutyronitrile.

[0024] In one embodiment of the present invention, the lithium salt in step S1 is selected from at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium dioxalate borate, and lithium difluorooxalate borate.

[0025] In one embodiment of the present invention, the inert atmosphere in step S2 is argon or nitrogen.

[0026] In one embodiment of the present invention, the solution casting method in step S4 includes the following steps: dissolving the polymer matrix and conductive lithium salt in a polar solvent and stirring until completely dissolved to form a homogeneous solution; adding the fluorinated polyether active organic microparticles obtained in step S3 to the homogeneous solution, and then dispersing them by ultrasonication to obtain a stable suspension; casting the suspension onto the substrate surface and drying it in a vacuum environment to remove the polar solvent, thereby obtaining a composite polymer solid electrolyte membrane.

[0027] In one embodiment of the present invention, the polar solvent is at least one selected from acetone, N-methylpyrrolidone, N,N-dimethylformamide, dimethyl sulfoxide, and N,N-dimethylacetamide; the vacuum drying temperature is 65°C to 120°C, and the drying time is 6.5h to 24h.

[0028] In one embodiment of the present invention, the dry hot rolling method in step S4 includes the following steps: mixing polymer matrix powder, fluorinated polyether active organic microparticles obtained in step S3, and conductive lithium salt direct dry powder to obtain a mixed powder; placing the mixed powder in a mold and hot rolling or hot pressing at 65℃~120℃ and 50MPa~300MPa for 5min~45min; cooling to room temperature to obtain a composite polymer solid electrolyte membrane.

[0029] A third aspect of the present invention provides a solid-state lithium battery comprising the above-described composite polymer solid electrolyte.

[0030] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0031] 1. The composite polymer solid electrolyte provided by this invention uses fluorinated polyether active organic microparticles, which belong to the same organic system as the fluorinated polymer matrix, as the reinforcing phase filler. It abandons the traditional inorganic filler. The two can undergo molecular-level physical entanglement and wetting, eliminating the micropores and interface defects that are common in inorganic-organic composites, and constructing a continuous, low-impedance lithium-ion transport channel. This fundamentally solves the problem of poor compatibility between inorganic fillers and polymer matrix and reduces interface impedance.

[0032] 2. In the composite polymer solid electrolyte provided by the present invention, the ether oxygen segment in the fluorinated polyether active organic microparticles can promote lithium salt dissociation and provide more lithium ion migration sites. The introduction of microparticles also reduces the crystallinity of the polymer matrix and increases the proportion of amorphous regions, thereby improving the ion transport capability of the composite polymer solid electrolyte.

[0033] 3. The fluorine-containing structure in the fluorinated polyether active organic microparticles of this invention can improve the oxidation stability of the material, giving the composite polymer solid electrolyte a wider electrochemical stability window. Its oxidation stability potential can reach 4.6V, which can meet the application requirements of high-voltage cathode material systems. At the same time, the fluorine-containing structure has an antioxidant protection effect at the cathode interface, giving the assembled full battery excellent cycle stability, with almost no capacity decay after 200 cycles.

[0034] 4. The composite polymer solid electrolyte provided by this invention, with its all-organic composite system, avoids the problems of inorganic particle sedimentation and membrane embrittlement, giving the electrolyte membrane both good flexibility and mechanical strength, which can effectively meet the mechanical strength requirements of the electrolyte membrane during solid-state battery assembly.

[0035] 5. The preparation method of the composite polymer solid electrolyte provided by the present invention is simple and has strong material system compatibility: the solution casting method does not require special equipment, and the dry hot rolling method has no solvent residue, is environmentally friendly and efficient, both of which meet the requirements of industrial-scale production. Moreover, the preparation process is highly controllable and the electrolyte membrane has high performance stability, and has good prospects for industrial application. Attached Figure Description

[0036] Figure 1 A microscopic schematic diagram of a composite encapsulation structure reinforced with fluorinated polyether active organic microparticles.

[0037] Figure 2 The image shows a scanning electron microscope (SEM) image of fluorinated polyether active organic microparticles, illustrating the particle size and morphology.

[0038] Figure 3 This is a comparison graph of EIS impedance tests for Example 2 and Comparative Example 1;

[0039] Figure 4 This is a comparison chart of the full-cell cycle performance tests of Example 2 and Comparative Example 1.

[0040] Figure 5 The graph shows the full-cell cycle performance of the composite polymer solid electrolyte membrane provided in Example 3.

[0041] Figure 6 The effect of the proportion of fluorinated polyether active organic microparticles on the performance of electrolyte membranes;

[0042] Figure 7 A comparison of stress-strain curves for different materials during the tensile process. Detailed Implementation

[0043] In this document, the range expressed as "from one value to another" is a concise way of representing a range to avoid listing all the values ​​in that range in the specification. Therefore, the description of a particular range of values ​​covers any value within that range as well as the smaller range of values ​​defined by that value, just as if the arbitrary value and the smaller range of values ​​were explicitly stated in the specification.

[0044] Fluoropolymer solid electrolytes, represented by polyvinylidene fluoride (PVDF) and polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), suffer from low room-temperature ionic conductivity due to their highly regular molecular chains and tendency to crystallize. Lithium ions primarily migrate through limited amorphous regions. Furthermore, during long-term cycling, the electrolyte-electrode interface tends to develop significant and continuously increasing interfacial impedance. To address these shortcomings, current technologies commonly employ inorganic ceramic fillers (such as Al₂O₃, SiO₂, LLZO, and LLZSP) to modify the polymer matrix. However, the interfacial properties of inorganic materials and organic polymers differ significantly, resulting in poor compatibility. During the composite process, particle agglomeration, interfacial voids, and localized phase separation easily occur, further increasing ion transport impedance. Moreover, the high density of inorganic ceramics, when added in large proportions, reduces the membrane's mass energy density and exacerbates membrane embrittlement, hindering flexible solid-state batteries and large-scale manufacturing. The technical problem to be solved by this invention is to overcome the inherent defects of poor compatibility between inorganic fillers and polymer matrix and easy agglomeration and embrittlement, while improving the ionic conductivity of composite polymer solid electrolyte, reducing interfacial impedance, and taking into account the mechanical flexibility and electrochemical stability of the membrane.

[0045] The composite polymer solid electrolyte provided by this invention abandons the traditional inorganic filler modification route and instead uses a fully organic fluorinated polyether active organic microparticle as the reinforcing phase filler. This fluorinated polyether active organic microparticle is prepared by bulk free radical polymerization copolymerization of polyethylene glycol methyl ether methacrylate (PEGMA) and fluorinated acrylate monomers, followed by grinding and sieving to obtain microparticles with a particle size of 200 nm to 5 μm. These microparticles are then combined with a fluorinated polymer matrix (PVDF, PVDF-HFP, etc.) and a conductive lithium salt, and can be formed into a composite polymer solid electrolyte membrane by solution casting or dry hot rolling.

[0046] Since the fluorinated polyether active organic microparticles and the fluorinated polymer matrix are both organic systems, they can undergo molecular-level physical entanglement and wetting, eliminating the microscopic pores and interface defects commonly found in inorganic-organic composites, thus constructing a continuous, low-impedance lithium-ion transport channel. The ether oxygen segments in the microparticles promote lithium salt dissociation and provide more lithium-ion migration sites. The introduction of the microparticles also reduces the crystallinity of the polymer matrix and increases the proportion of amorphous regions, thereby significantly improving ionic conductivity and reducing interface impedance. The fluorinated structure in the microparticles improves the oxidative stability of the material and broadens the electrochemical stability window. Furthermore, the all-organic composite system avoids the problems of inorganic particle sedimentation and membrane embrittlement, giving the membrane both good flexibility and mechanical strength. Measurements show that the room-temperature ionic conductivity of the composite polymer solid electrolyte membrane of this invention can reach approximately 4 × 10⁻⁶. - 4 The S / cm level, the symmetric cell interface impedance is as low as about 16.5Ω, the oxidation stability potential reaches 4.6V, the tensile strength is above 3.2MPa, and the assembled LFP|Li full cell has virtually no capacity decay after 200 cycles. Its overall performance is superior to pure polymer membranes and inorganic composite membranes.

[0047] The applicant discovered that the fundamental reason why existing inorganic filler modification schemes have limited improvement in ionic conductivity and high interfacial impedance is not due to insufficient lithium conduction capacity of the filler itself, but rather to compatibility defects caused by the difference in interfacial properties between the inorganic filler and the organic polymer. Specifically, it is difficult for inorganic particles and organic segments to achieve molecular-level wetting and bonding, inevitably leaving pores, defects, and even phase separation regions at the interface. These regions, in turn, become high-impedance barriers for lithium-ion transport. Simultaneously, the aggregation and sedimentation of inorganic particles further deteriorate the uniformity of filler dispersion in the matrix. Based on this discovery, the inventors inferred that if the filler itself is an organic material, and its molecular structure simultaneously contains fluorinated structures compatible with the fluorinated polymer matrix and ether oxygen segments that promote lithium salt dissociation, it is possible to fundamentally eliminate the interfacial compatibility defects. Therefore, the inventors selectively copolymerized PEGMA with ether oxygen segments with fluorinated acrylate monomers, resulting in microparticles that simultaneously possess the dual functions of "fluorine-containing—compatibility / enhanced oxidation stability" and "polyether—promoting dissociation / conducting lithium." Furthermore, by bulk polymerization into blocks followed by grinding and sieving, the microparticles were processed into active microparticle fillers with controllable particle size (200nm–5μm) to ensure uniform composite with the polymer matrix. Comparative experiments in the examples and comparative examples verified that the composite membrane using these all-organic fluorinated polyether active microparticles exhibited significantly improved ionic conductivity, interfacial impedance, mechanical properties, and cycle stability compared to the pure PVDF-HFP membrane (Comparative Example 1) and the PVDF-LLZSP inorganic composite membrane (Comparative Example 2).

[0048] For ease of understanding, some terms used in this application are defined as follows:

[0049] Fluorinated polyether active organic microparticles refer to organic solid microparticles with a particle size of 200 nm to 5 μm obtained by free radical copolymerization of polyethylene glycol methyl ether methacrylate (PEGMA) and fluorinated acrylate monomers, followed by grinding and sieving. Their molecular structure contains both polyether (ether oxygen) segments derived from PEGMA and fluorinated structures derived from fluorinated acrylate monomers. The polyether segments and fluorinated polar structures in these active organic microparticles can form a stable physicochemical coupling relationship with lithium salts and the polymer matrix through interactions. Specifically, the ether oxygen in the polyether segments can reversibly coordinate with lithium ions, promoting lithium salt dissociation and ion migration; the fluorinated structures can regulate the surface polarity and interfacial stability of the microparticles, improving the oxidative stability of the electrolyte. Therefore, these active organic microparticles have stronger interfacial regulation and ion transport promotion capabilities compared to traditional inert inorganic fillers. In this application, "fluorinated polyether active organic microparticles" has the same meaning as "fluorinated polyether active organic powder" and "organic functional microparticles."

[0050] Example 1

[0051] This embodiment provides a method for preparing fluorinated polyether active organic microparticles, including the following steps:

[0052] (1) Weigh 10g of polyethylene glycol methyl ether methacrylate (PEGMA) monomer, 1.4g of trifluoroethyl methacrylate (TFEMA, as a fluorinated acrylate monomer), 2.2g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and 0.1g of azobisisobutyronitrile (AIBN, as a thermal initiator), and mix the above raw materials thoroughly to obtain a mixed raw material; the above ratio corresponds to a mass ratio of PEGMA:fluorinated acrylate monomer:lithium salt:initiator of 100:14:22:1. In this embodiment, polyethylene glycol methyl ether methacrylate has a Mw≈475 and its general structural formula is CH2=C(CH3)COO(CH2CH2O). n CH3, where n is 8~10. Specifically, the polyethylene glycol methyl ether methacrylate in the examples is polyethylene glycol methyl ether methacrylate with the brand name PEGMA475 produced by Adamas.

[0053] (2) Place the mixed raw materials in an argon-protected reactor, heat to 70°C, and carry out bulk free radical polymerization for 8 hours. After the reaction is completed, cool to room temperature to obtain fluorinated polyether copolymer blocks.

[0054] (3) The fluorinated polyether copolymer block was crushed by a micro air jet mill and preliminarily classified by a 1500-2000 mesh sieve to obtain particles with a particle size of less than 5 μm, and fluorinated polyether active organic microparticles were obtained and sealed for later use.

[0055] The microstructure of the fluorinated polyether active organic microparticles obtained in this embodiment is as follows: Figure 2 As shown, the particles are granular with a diameter of approximately 4 μm.

[0056] Example 2

[0057] This embodiment provides a method for preparing a composite polymer solid electrolyte membrane.

[0058] Specifically, this embodiment uses a solution casting method to prepare a composite polymer solid electrolyte membrane, including the following steps:

[0059] (1) Weigh 0.4g of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) as the polymer matrix and 0.5g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) as the conductive lithium salt. Add 10mL of N,N-dimethylformamide (DMF) solvent and stir at 40℃ for 1.5h until completely dissolved to form a homogeneous solution.

[0060] (2) Add 0.3g of the fluorinated polyether active organic microparticles prepared in Example 1 to the above homogeneous solution, and use ultrasonic dispersion to uniformly disperse the microparticles to obtain a stable suspension.

[0061] (3) The suspension was cast onto the surface of the polytetrafluoroethylene substrate and the coating thickness was controlled to be 500 μm. It was placed in a vacuum drying oven and dried at 65°C for 12 h to remove the DMF solvent and obtain a composite polymer solid electrolyte membrane.

[0062] In this embodiment, the proportion of fluorinated polyether active organic microparticles (0.3g) to the total mass of the polymer matrix and polymeric organic microparticles (0.4g + 0.3g = 0.7g) is approximately 42.86 wt%, the proportion of conductive lithium salt (0.5g) to the total mass of the composite polymer solid electrolyte is approximately 41.67 wt%, and the proportion of polymer matrix (0.4g) to the total mass of the composite polymer solid electrolyte is approximately 33.33 wt%.

[0063] Following the above steps, the resulting slurry is a semi-transparent colloidal substance with good uniformity and rheological properties. It shows no sedimentation after standing for 24 hours and forms a dense and smooth film when cast. The resulting composite polymer solid electrolyte membrane exhibits good flexibility and tensile strength. Electrochemical impedance spectroscopy (EIS) at 25°C shows a room temperature ionic conductivity of approximately 4.23 × 10⁻⁶. -4 With a low S / cm and low interfacial impedance, the oxidation stability window of a lithium steel test cell (used as a coin cell structure for linear scanning voltammetry, stainless steel sheet | electrolyte membrane | lithium sheet, such as the SS / SSE / Li LSV test system, a generalized half cell, used only for testing oxidation potential) is tested using linear scanning voltammetry (LSV). The scan range is 2.5-6.0V, and the tested oxidation decomposition potential reaches above 4.6V.

[0064] It should be noted that, in optional embodiments, the polymer matrix is ​​not limited to PVDF-HFP, but may also be selected from one or more of PVDF, PAN, and PMMA; the conductive lithium salt is not limited to LiTFSI; the polar solvent is not limited to DMF, but may also be one or more of acetone, NMP, DMSO, and DMA; the vacuum drying temperature may be selected between 65°C and 120°C, and the drying time may be selected between 6.5h and 24h.

[0065] Example 3

[0066] This embodiment provides a method for preparing a composite polymer solid electrolyte membrane.

[0067] Specifically, this embodiment uses a dry hot rolling method to prepare a composite polymer solid electrolyte membrane, including the following steps:

[0068] (1) Weigh 0.3g of polyvinylidene fluoride (PVDF) powder as the polymer matrix, 0.3g of fluorinated polyether active organic microparticles prepared in Example 1, and 0.4g of lithium difluorosulfonyl imide (LiFSI) as the conductive lithium salt, place them in a high-speed mixer, mix at room temperature for 15min, and obtain a uniformly mixed powder.

[0069] (2) Load the mixed powder into the mold, place it in the hot press, and hot press it at 110℃ and 200MPa for 20 minutes.

[0070] (3) Maintain pressure and cool to room temperature, then demold to obtain composite polymer solid electrolyte membrane.

[0071] The resulting composite polymer solid electrolyte membrane, obtained through the above steps, exhibits good mechanical strength. EIS testing at 25°C shows its room-temperature ionic conductivity to be approximately 3.97 × 10⁻⁶. -4 With a voltage S / cm and low interfacial impedance, the oxidation stability window of lithium steel batteries was tested using linear sweep voltammetry (LSV) in a range of 2.5-6.0V, and the tested oxidation decomposition potential reached above 4.7V.

[0072] It should be noted that, in the optional embodiments, the hot pressing temperature can be selected between 65℃ and 120℃, the pressure between 50MPa and 300MPa, and the heat and pressure holding time between 5min and 45min. Comparative Example 1

[0073] This comparative example provides a pure PVDF-HFP solid electrolyte membrane, prepared by the following method:

[0074] (1) Weigh 0.7g PVDF-HFP and 0.5g LiTFSI, dissolve them in 10mL DMF, and stir at 45℃ for 1h until completely dissolved to form a homogeneous solution.

[0075] (2) The homogeneous solution was cast onto the surface of the polytetrafluoroethylene substrate and the coating thickness was controlled to be 500 μm. It was placed in a vacuum drying oven and dried at 65°C for 12 h to remove the DMF solvent and obtain a pure PVDF-HFP solid electrolyte membrane.

[0076] The resulting membrane, obtained through the above steps, is transparent and soft, but exhibits severe crystallization at room temperature. EIS testing at 25°C revealed a room-temperature ionic conductivity of only approximately 1.43 × 10⁻⁶. -4 The oxidation stability window of lithium steel batteries was tested using linear sweep voltammetry (LSV) with a sweep range of 2.5-6.0V and an oxidation decomposition potential of 4.2V.

[0077] Comparative Example 2

[0078] This comparative example provides a PVDF-LLZSP inorganic composite electrolyte membrane, prepared by the following method:

[0079] (1) Weigh 0.4g PVDF-HFP and 0.5g LiTFSI, dissolve them in 10mL DMF, and stir at 50℃ for 1h until completely dissolved to form a homogeneous solution.

[0080] (2) Add 0.3g of lithium lanthanum zirconium silicon phosphorus (LLZSP) inorganic powder to the above homogeneous solution, and use ultrasonic dispersion to uniformly disperse the powder to obtain a stable suspension.

[0081] (3) The suspension was cast onto the surface of the polytetrafluoroethylene substrate and the coating thickness was controlled to be 500 μm. It was placed in a vacuum drying oven and dried at 65°C for 12 h to remove the DMF solvent and obtain the PVDF-LLZSP composite electrolyte membrane.

[0082] Following the above steps, the ceramic particles tend to settle in the slurry, leading to increased brittleness after film formation. EIS testing at 25°C showed a room temperature ionic conductivity of approximately 3.17 × 10⁻⁻⁻⁶. 4 S / cm, but due to the high density of ceramics, the membrane is relatively heavy overall. Therefore, linear sweep voltammetry (LSV) was used to test the oxidation stability window of lithium steel batteries, with a scan range of 2.5-6.0V and a test oxidation decomposition potential of 4.0V.

[0083] Comparative Example 3

[0084] This comparative study investigates the effect of the proportion of fluorinated polyether active organic particles in the composite polymer solid electrolyte membrane in Example 2.

[0085] Specifically, this comparative example also uses the solution casting method to prepare composite polymer solid electrolyte membranes, and the study includes the following:

[0086] For the fluorinated polyether active organic microparticles prepared in Example 1, compare the content of 0wt%-100wt% (for the total mass of the fluorinated polyether active organic microparticles and the polymer matrix).

[0087] Based on the comparative experiments described above, all data obtained in this comparative example, through experiments with different addition ratios, revealed that as the content of fluorinated polyether active organic microparticles increased, the ionic conductivity of the composite solid electrolyte exhibited a trend of first rapidly increasing and then stabilizing. When the addition amount was below 5 wt%, the content of functional microparticles was insufficient, resulting in limited interface regulation and ion transport promotion effects; when the addition amount exceeded 50 wt%, although ion transport performance continued to improve, the excessively high proportion of organic microparticles led to a reduction in the continuous polymer phase, resulting in a decrease in the mechanical integrity of the membrane. Therefore, controlling the content of fluorinated polyether active organic microparticles within the range of 5–50 wt% is recommended. Figure 6 As shown.

[0088] Example 1 of this experiment tested the structure and function of fluorinated polyether active organic microparticles. The results showed that PEGMA ether segments and fluorinated structural units were successfully introduced into the obtained active organic microparticles, forming a stable bond rather than a simple physical mixture. Furthermore, the introduction of active organic microparticles effectively modulated the polymer matrix structure, which is beneficial for ion migration. In addition, the particle size distribution of the obtained organic microparticles was able to achieve uniform dispersion in the composite electrolyte system.

[0089] This experiment demonstrates battery assembly and performance testing of the electrolyte membranes obtained in Examples 2 and 3 and Comparative Examples 1 and 2, with the following results.

[0090] (a) Ionic conductivity test

[0091] The ionic conductivity of each membrane was measured at 25°C using an electrochemical workstation via electrochemical impedance spectroscopy (EIS). The results showed that the room temperature ionic conductivity of Examples 2, 3, Comparative Example 1, and Comparative Example 2 was 4.23 × 10⁻⁶. -4 S / cm, 3.97×10 -4 S / cm, 1.43×10 -4 S / cm, 3.17×10 -4 S / cm. It is evident that the ionic conductivity of Examples 2 and 3, which utilize fluorinated polyether active organic microparticles, is significantly improved compared to the pure PVDF-HFP membrane (Comparative Example 1), and superior to the inorganic composite membrane (Comparative Example 2). This is because the molecular-level compatibility of the fluorinated polyether active organic microparticles with the polymer matrix reduces the polymer crystallinity and increases the proportion of amorphous regions. Furthermore, the ether oxygen segments promote lithium salt dissociation and provide more lithium ion migration sites, such as... Figure 1 As shown, fluorinated polyether active organic microparticles form a molecular-level interface bond with the polymer matrix, and the microparticles are continuously encapsulated by the polymer matrix, thereby constructing a continuous, low-impedance lithium-ion transport channel.

[0092] (ii) Interface impedance test

[0093] The interface impedance of the symmetrical cell was tested using EIS. The comparison results of the EIS impedance tests in Example 2 and Comparative Example 1 are as follows: Figure 3 As shown. The interfacial impedances of Examples 2, 3, Comparative Example 1, and Comparative Example 2 are 16.5Ω, 21Ω, 62Ω, and 40Ω, respectively. It can be seen that the all-organic composite system of the present invention (Examples 2 and 3) significantly reduces the interfacial contact resistance due to the formation of an organic-organic interface, and its interfacial impedance is significantly lower than that of the pure polymer film (Comparative Example 1) and the inorganic composite film (Comparative Example 2).

[0094] (III) Mechanical performance testing

[0095] Tensile properties of various composite electrolyte membranes were tested using a universal testing machine to investigate the effects of different components on the mechanical properties of the electrolyte membranes. The results are shown in the table below. Figure 7 As shown.

[0096] sample Composition characteristics Tensile strength / MPa Elongation at break / % evaluate Example 2 Casting polymer membrane 3.21 46.8 A balance of flexibility and strength, resulting in optimal overall mechanical properties. Example 3 Hot-pressed polymer film 3.58 52.4 A balance of flexibility and strength, resulting in optimal overall mechanical properties. Comparative Example 1 Inactive organic particle polymer system 2.17 31.6 Insufficient strength and toughness Comparative Example 2 LZSP Inorganic Packing System 2.63 18.9 Increased rigidity but significantly more brittle

[0097] The composite electrolyte membranes obtained by this invention (Examples 2 and 3) exhibit good flexibility and structural integrity, meeting the mechanical strength requirements of electrolyte membranes during solid-state battery assembly. Simultaneously, the fluorinated polyether active organic microparticles demonstrate good compatibility with the polymer matrix, enabling uniform dispersion within the polymer system and contributing to improved mechanical stability of the composite electrolyte membrane. Compared to traditional inorganic filler systems (such as LLZSP in Comparative Example 2), the system of this invention reduces the risk of interfacial defects and membrane embrittlement caused by rigid fillers.

[0098] (iv) Electrochemical stability window test

[0099] The fluorinated structure in the fluorinated polyether active organic microparticles exhibits high bond energy and electronic stability, reducing the tendency of polymer segments to undergo oxidative decomposition under high-potential conditions. Simultaneously, the ether oxygen structure in the polyether segments can improve the lithium salt dissociation state and enhance the internal structural uniformity of the composite electrolyte, thereby improving overall electrochemical stability. This indicates that the fluorinated structure can improve the oxidation stability of the material. The composite polymer solid electrolyte membrane obtained in Example 2 achieves an oxidation stability potential of 4.6V, meeting the application requirements of high-voltage cathode material systems.

[0100] (v) Full battery cycle performance test

[0101] Using lithium iron phosphate (LFP) as the positive electrode (active loading of 1.5-2.0 mg) and lithium metal (Li) as the negative electrode, an LFP|Li all-solid-state battery was assembled using the electrolyte membrane of this invention. Cyclic performance tests were conducted at 25°C, with all tests performed at a 1C rate and a voltage range of 2.6-3.2V. The comparison results of the full-cell cycle performance tests between Example 2 and Comparative Example 1 are as follows: Figure 4 As shown, the full-cell cycle performance test graph of Example 3 is as follows. Figure 5 As shown. For the LFP|Li full cell assembled in Example 2, due to the antioxidant protection effect of the fluorinated polyether active organic microparticle filler at the positive electrode interface, the capacity of the battery showed almost no decay after 200 cycles, which is significantly better than the traditional PVDF system. In contrast, the LFP|Li full cell assembled in Comparative Example 2 had a capacity retention rate of less than 90% after cycling; the membrane assembly obtained in Comparative Example 1 showed extremely high bulk impedance in the steel cell, and the assembled full cell could not operate normally at room temperature.

[0102] The test results above show that this invention, by introducing fully organic fluorinated polyether active organic microparticles as reinforcing phase fillers, achieves synergistic improvements in ion transport performance, mechanical properties, electrochemical stability, and interfacial compatibility. This overcomes the problems of insufficient ionic conductivity and high interfacial impedance in existing polymer solid electrolytes, as well as the poor compatibility, easy agglomeration, and embrittlement of inorganic fillers. Furthermore, the preparation process of this invention is simple; the solution casting method requires no special equipment, and the dry hot rolling method leaves no solvent residue. The material system has strong compatibility, meeting the requirements for large-scale industrial production and possessing good prospects for industrial application. It can be applied to the field of high-safety, high-energy-density solid-state lithium batteries.

[0103] Under the guidance of the present invention and the above embodiments, those skilled in the art will readily foresee that all the raw materials or their equivalents, processing methods or their equivalents listed or exemplified in the present invention can achieve the present invention, and that the upper and lower limits and range values ​​of the parameters of each raw material and processing method can also achieve the present invention. Examples are not listed one by one here.

Claims

1. A composite polymer solid electrolyte, characterized in that, include: Polymer matrix; Fluorinated polyether active organic microparticles, wherein the fluorinated polyether active organic microparticles are prepared by copolymerization of polyethylene glycol methyl ether methacrylate and fluorinated acrylate monomers, and the particle size is 200 nm to 5 μm; Conductive lithium salt; The lithium salt accounts for 20wt% to 50wt% of the total mass of the composite polymer solid electrolyte, the fluorinated polyether active organic microparticles account for 2.5wt% to 40wt% of the total mass of the composite polymer solid electrolyte, and the remainder is the polymer matrix.

2. The composite polymer solid electrolyte according to claim 1, characterized in that, The general structural formula of the polyethylene glycol methyl ether methacrylate is CH2=C(CH3)COO(CH2CH2O). n CH3, where n is 3 to 20.

3. The composite polymer solid electrolyte according to claim 1, characterized in that, The polymer matrix is ​​selected from at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyacrylonitrile, and polymethyl methacrylate; The fluorinated acrylate monomer is trifluoroethyl methacrylate; The conductive lithium salt is at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium dioxalateborate, and lithium difluorooxalateborate.

4. A method for preparing the composite polymer solid electrolyte according to any one of claims 1 to 3, characterized in that, Includes the following steps: Step S1: Polyethylene glycol methyl ether methacrylate, fluorinated acrylate monomers, lithium salt and thermal initiator are mixed in a mass ratio of 100:(10-20):(10-40):(0.8-2) to obtain a mixed raw material; Step S2: Bulk free radical polymerization is carried out at 60℃~100℃ for 5.5h~24h under an inert atmosphere, and polymer bulk is obtained after the reaction is completed; Step S3: Grind and sieve the polymer block to obtain fluorinated polyether active organic microparticles with a particle size of 200 nm to 5 μm after sieving. In step S4, a composite polymer solid electrolyte membrane is formed by using a solution casting method or a dry hot rolling method to combine the polymer matrix, the fluorinated polyether active organic microparticles obtained in step S3, and the conductive lithium salt.

5. The preparation method according to claim 4, characterized in that, In step S1, the thermal initiator is azobisisobutyronitrile; The lithium salt is selected from at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium dioxalateborate, and lithium difluorooxalateborate.

6. The preparation method according to claim 4, characterized in that, The inert atmosphere mentioned in step S2 is argon or nitrogen.

7. The preparation method according to claim 4, characterized in that, The solution casting method in step S4 includes the following steps: dissolving the polymer matrix and conductive lithium salt in a polar solvent and stirring until completely dissolved to form a homogeneous solution; adding the fluorinated polyether active organic microparticles obtained in step S3 to the homogeneous solution, and then dispersing them by ultrasonication to obtain a stable suspension; casting the suspension onto the substrate surface and drying it in a vacuum environment to remove the polar solvent to obtain a composite polymer solid electrolyte membrane.

8. The preparation method according to claim 7, characterized in that, The polar solvent is at least one of acetone, N-methylpyrrolidone, N,N-dimethylformamide, dimethyl sulfoxide, and N,N-dimethylacetamide; the vacuum drying temperature is 65℃~120℃, and the drying time is 6.5h~24h.

9. The preparation method according to claim 4, characterized in that, The dry hot rolling method described in step S4 includes the following steps: mixing polymer matrix powder, fluorinated polyether active organic microparticles obtained in step S3, and conductive lithium salt direct dry powder to obtain a mixed powder; placing the mixed powder in a mold and hot rolling or hot pressing at 65℃~120℃ and 50MPa~300MPa for 5min~45min; cooling to room temperature to obtain a composite polymer solid electrolyte membrane.

10. A solid-state lithium battery, characterized in that, The composite polymer solid electrolyte comprising any one of claims 1-3.